Transforming Islamic Religious Education Learning through Differentiated Learning in the Merdeka Curriculum - Edi Nurhidin; Maimunatun Habibah (Kognisi: Jurnal Ilmu Keguruan, 2024)
This paper investigates the transformation of Islamic religious education (PAI) learning through differentiated learning in the Merdeka Curriculum setting. The curriculum, heralding a shift towards contemporary educational paradigms, aims to cater to individual student differences through enhanced personalized learning strategies. This paper used a qualitative research method, using literature type by collecting data from books, journal articles, conference or seminar papers, and other publications related to three main concepts: differentiated learning, Islamic religious education, and the Merdeka Curriculum. The findings highlight three significant insights. Firstly, the emphasis on personalized learning, as viewed by Tomlinson, is crucial for adapting education to meet diverse student needs, including their readiness, interest, and learning environment, a key principle of the Merdeka Curriculum. This curriculum supports such individualized strategies and represents a significant shift towards enhancing learning experiences. Secondly, this curriculum's alignment with differentiated learning is evident in its promotion of learner-centered approaches, making education more inclusive and effective. Thirdly, applying differentiated learning in Islamic Religious Education (PAI) within the Merdeka Curriculum framework demonstrates a dynamic approach to catering to diverse student requirements, thus fostering deeper engagement and comprehension in PAI subjects. This study confirms a meaningful link between differentiated learning and the Merdeka Curriculum's goals, indicating a progressive direction for PAI learning, potentially improving educational outcomes and challenging traditional Islamic education methods. This study posits differentiated learning as a key strategy in actualizing the goals of the Merdeka Curriculum, thus significantly contributing to the ongoing discourse on educational reform in Indonesia.